Lithium diaphragm as well as preparation method and application thereof
By using a lithiated separator containing Li+ embedded inorganic substances in lithium metal batteries, combined with electrochemical prelithiation treatment, the problem of low Coulomb efficiency and short cycle life in ester-based electrolytes is solved, and a higher Safety and cycle stability.
Patent Information
- Application Number
- CN202411613398.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
AI Technical Summary
Existing lithium metal batteries have problems with low Coulomb efficiency (CE) and short cycle life in ester-based electrolytes, and are insufficient in safety, resulting in the risk of rapid growth of lithium dendrites and diaphragm penetration.
A lithiated diaphragm is used, which consists of a base film and an inorganic coating containing Li+ embedded. The chemical formula of the Li+ embedded inorganic substance of the coating is LixAaBb-δ, AaBb represents an inorganic substance, 0
通过提高锂离子的均匀传输和分布,延长了电池的循环寿命,并增强了电池的安全性,提高了库仑效率和热稳定性。
Smart Images

Figure CN119447702A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium metal batteries, and in particular to a lithiated diaphragm and a preparation method and application thereof. Background Art
[0002] Lithium metal has a low density (0.534 g / cm 3 ), high theoretical capacity (3860mA h / g), and low standard electrode potential (-3.04V relative to hydrogen standard electrode potential), making it an ideal anode material for achieving high energy density batteries. However, lithium metal anodes have multiple instabilities during cycling, including electrolyte decomposition and excessive growth of lithium dendrites during continuous electroplating and stripping, which not only increases the specific surface area of the lithium metal anode and accelerates the growth of lithium dendrites, but also causes the limited amount of electrolyte to be rapidly consumed, thus causing serious safety hazards. Therefore, in order to extend the cycle life and improve the safety of lithium metal batteries (LMBs), it is crucial to regulate the uniform electroplating of lithium ions and improve the coulombic efficiency (CE). Ester-based electrolytes are considered to be promising electrolytes for commercial LMBs because of their wide electrochemical window, low cost, and high boiling point / flash point. However, the fragile SEI of lithium metal anodes in ester-based electrolytes and the unstable Li+ transport at the interface lead to low CE, continuous growth of lithium dendrites, and short cycle life. At present, there have been a lot of improvements focused on alloy anodes, electrolytes, lithium salts, additives, separators, etc. These works have been proven to inhibit the growth of lithium dendrites, but their development is inhibited by relatively complex process conditions and high costs. Therefore, it is critical to seek a low-cost, multifunctional method to improve the cycle life and safety of LMB in ester-based electrolytes.
[0003] As one of the key components of lithium metal batteries, the main function of the separator is to prevent the positive and negative electrodes from directly contacting each other and causing a short circuit. + The transport of lithium metal is closely related to the electroplating / stripping of lithium metal. Currently, most commercial separators are made of polyolefin compounds such as polypropylene (PP), polyethylene (PE), and related PE / PP composites. Such separators usually have poor wettability, thermal stability, and unevenly distributed pores. These factors will lead to Li + Uneven distribution exacerbates the concentration polarization on the electrode surface, causing lithium dendrites to grow rapidly and pierce the separator, causing huge safety hazards. Previous research on separators has mainly focused on surface coating, electrospinning, chemical and physical surface treatment, etc. These methods have been proven to enhance the wettability with the electrolyte to a certain extent, improve thermal stability and improve Li + flux, thereby achieving the purpose of inhibiting the growth of lithium dendrites. However, these improvements have +The deposition and transport of lithium metal batteries have limited effects, and the battery also requires more electrolyte and the N / P ratio cannot be reduced, which has little effect on improving CE and increasing the safety of LMB. Therefore, how to improve the CE and safety of lithium metal batteries at the same time is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application provides a lithiated diaphragm and a preparation method and application thereof to solve the following technical problem: how to simultaneously improve the CE and safety of lithium metal batteries.
[0005] In a first aspect, the present application provides a lithiated separator, the lithiated separator comprising:
[0006] basement membrane; and
[0007] A coating layer is attached to at least a portion of the separator, wherein the coating layer contains Li + The embedded inorganic + The chemical formula of the embedded inorganic substance is Li x A a B b-δ , where A a B b Represents inorganic matter, 0<x<a; 0<δ<b.
[0008] Optionally, the Li + The embedded inorganic matter has an amorphous structure.
[0009] Optionally, the Li + The embedded inorganic substances include: Li x TiO 2-δ , Li x ZnO 1-δ , Li x SnO 2-δ and Li x MnO 2-δ At least one of .
[0010] Optionally, the Li + The embedded inorganic loading is > 0 and ≤ 1.6 mg / m 2 .
[0011] Optionally, the thickness of the coating is greater than 0 and less than or equal to 10 μm.
[0012] Optionally, the base film is a polyolefin membrane, and the polyolefin membrane includes: a polyethylene membrane, a polypropylene membrane, and a polyethylene and polypropylene composite membrane.
[0013] In a second aspect, the present application provides a method for preparing a lithiated separator according to any one embodiment of the first aspect, the method comprising:
[0014] Mixing an inorganic filler, polyvinylidene fluoride and a solvent to obtain a mixed slurry;
[0015] Applying the mixed slurry to at least a portion of the base film to form the coating to obtain a composite diaphragm;
[0016] The composite membrane is electrochemically pre-lithiated to obtain a lithiated membrane.
[0017] Optionally, the mass ratio of the inorganic filler to polyvinylidene fluoride is (7-9):(1-3).
[0018] Optionally, the mass concentration of the polyvinylidene fluoride is 30 mg / mL to 70 mg / mL.
[0019] In a third aspect, the present application provides a lithium metal battery, wherein the lithium metal battery comprises the lithiated separator described in any one of the embodiments in the first aspect.
[0020] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0021] The present application provides a lithiated diaphragm, which comprises: a base film; and a coating, wherein the coating is attached to at least a portion of the diaphragm, and the coating contains Li + The embedded inorganic + The chemical formula of the embedded inorganic substance is Li x A a B b-δ , where A a B b represents inorganic matter, 0<x<a; 0<δ<b. The base film of the lithiated diaphragm serves as a support to ensure the mechanical strength and stability of the diaphragm. The coating is attached to at least part of the base film and contains Li + The embedded inorganic coating structure has highly uniform ion channels at the nanoscale, which is beneficial for Li + At the same time, due to the large amount of Li + The metal ions of inorganic materials are reduced, the crystal structure of inorganic materials is missing, a large number of oxygen vacancies are generated, and the reducibility is enhanced, so that the natural passivation layer on lithium metal can react preferentially, reducing the nucleation overpotential. The construction of a diaphragm with multiple oxygen vacancy sites is conducive to the dissociation of lithium salts, increasing the migration number of lithium ions, and promoting the uniform distribution of lithium ions. In addition, the Lego brick structure formed after electroplating effectively protects the diaphragm from being penetrated by dendrites. Thereby, the CE and safety of lithium metal batteries are improved at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0024] Figure 1 A schematic diagram of a process for preparing a lithiated separator provided in an embodiment of the present application;
[0025] Figure 2 This is an optical photograph of the lithiated separator provided in Example 1 of the present application;
[0026] Figure 3 Li on the lithiated diaphragm provided in Example 1 of the present application x TiO 2-δ TEM images of particles;
[0027] Figure 4 Li on the lithiated diaphragm provided in Example 1 of the present application x TiO 2-δ XRD spectrum of particles;
[0028] Figure 5 The Li on the diaphragm provided in Example 1 and Comparative Example 1 of the present application x TiO 2-δ EPR spectra of particles and TiO2 particles;
[0029] Figure 6 The Li on the diaphragm provided in Example 1 and Comparative Example 1 of the present application x TiO 2-δ O1s high-resolution XPS spectra of particles and TiO2 particles;
[0030] Figure 7 A test diagram of a lithium symmetric battery using the diaphragm provided in Example 1 and Comparative Example 2 of the present application;
[0031] Figure 8 CE diagrams of the diaphragms provided in Examples 1 to 3 and Comparative Examples 1 to 2 of the present application;
[0032] Fig. 9 A full battery test diagram of the diaphragm provided in Example 1 and Comparative Examples 1 to 2 of the present application;
[0033] Fig.10 This is a rate performance test chart of the diaphragm provided in Example 1 and Comparative Examples 1 to 2 of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0036] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0038] The present application provides a lithiated diaphragm, the lithiated diaphragm comprising:
[0039] basement membrane; and
[0040] A coating layer is attached to at least a portion of the separator, wherein the coating layer contains Li + The embedded inorganic + The chemical formula of the embedded inorganic substance is Li x A a B b-δ , where A a B b Represents inorganic matter, 0<x<a; 0<δ<b.
[0041] The lithium ion diaphragm in this application is mainly composed of a base film and a coating. The base film serves as a support to ensure the mechanical strength and stability of the diaphragm. The coating is attached to at least part of the base film and contains Li + The embedded inorganic coating structure has highly uniform ion channels at the nanoscale, which is beneficial for Li + At the same time, due to the large amount of Li + The embedding of inorganic metal ions reduces the metal ions of inorganic materials, and the loss of inorganic crystal structure generates a large number of oxygen vacancies, which enhances the reducibility and allows the natural passivation layer on lithium metal to react preferentially, thus reducing the nucleation overpotential. The construction of a diaphragm with multiple oxygen vacancy sites is conducive to the dissociation of lithium salts, increases the migration number of lithium ions, and promotes the uniform distribution of lithium ions. In addition, the Lego brick structure formed after electroplating effectively protects the diaphragm from being penetrated by dendrites.
[0042] In summary, the lithium-ion separator prepared by the electrochemical pre-lithiation strategy in this application has excellent electrochemical performance and has the following advantages: (1) High average CE: The highly uniform ion channels in the amorphous coating are conducive to Li + (2) Long cycle life: The multi-oxygen vacancy sites in the coating promote the dissociation of lithium salts, increase the migration number of lithium ions, and promote the uniform distribution of lithium ions. These characteristics help reduce the formation and growth of lithium dendrites, thereby extending the cycle life of the battery. (3) Lego structure formed after electroplating: This unique structure effectively protects the diaphragm from being penetrated by lithium dendrites, further improving the safety and cycle stability of the battery.
[0043] The lithiated diaphragm of the present application has broad application prospects in lithium metal batteries and lithium ion batteries. Especially in the context of limited lithium resources, it provides strong support for achieving high-performance and long-life battery systems. In addition, the preparation method and electrochemical properties of the diaphragm also provide new ideas for the innovation and development of battery materials.
[0044] In some embodiments, the Li + The embedded inorganic matter has an amorphous structure.
[0045] Amorphous structure, also known as disordered structure or glassy structure, has disordered arrangement of atoms or molecules compared to crystal structure, without long-range order. This disorder leads to some unique physical and chemical properties of amorphous materials. Amorphous materials can provide more ion diffusion channels due to their special isotropic properties and efficient percolation paths. This makes Li +The diffusion rate in the electrode is increased, thereby improving the charge and discharge performance of the battery. At the same time, the disordered arrangement of atoms or molecules in the amorphous structure may lead to more electronic state density distribution, thereby enhancing the electronic conductivity of the material. This helps to reduce the internal resistance of the battery and improve the power output and energy efficiency of the battery. In addition, the disordered arrangement in the amorphous structure can produce more defects and vacancies, which can serve as Li + This increases the reversible capacity and cycling stability of the battery.
[0046] In some embodiments, the Li + The embedded inorganic substances include: Li x TiO 2-δ , Li x ZnO 1-δ , Li x SnO 2-δ and Li x MnO 2-δ At least one of .
[0047] In some embodiments, the Li + The embedded inorganic loading is > 0 and ≤ 1.6 mg / m 2 .
[0048] In some embodiments, the thickness of the coating is >0 and ≤10 μm.
[0049] In general, the greater the loading, the thicker the coating. + The embedded inorganic loading is > 0 and ≤ 1.6 mg / m 2 On the one hand, it can provide more lithium ion conduction channels, thereby accelerating the transmission speed of lithium ions. On the other hand, if the loading amount is greater than 1.6 mg / m 2 , the contact resistance between inorganic particles will increase, and the porosity inside the coating may decrease, causing the lithium ion transmission channel to become narrow or blocked, thereby reducing the transmission speed. If the thickness of the coating is greater than 10μm, the transmission distance and transmission resistance of lithium ions will increase, resulting in a slow transmission speed. For example, Li + The loading of embedded inorganic substances can be 0.01 mg / m 2 , 0.1mg / m 2 , 0.3mg / m 2 , 0.5mg / m 2 , 1mg / m 2 , 1.2mg / m 2 , 1.4mg / m 2 , 1.6mg / m 2The thickness of the coating can be 0.1μm, 1μm, 2μm, 3μm, 4μm, 6μm, 8μm, 10μm, etc.
[0050] In some embodiments, the base film is a polyolefin membrane, and the polyolefin membrane includes: a polyethylene membrane, a polypropylene membrane, and a polyethylene and polypropylene composite membrane.
[0051] Figure 1 A schematic flow chart of a method for preparing a lithiated diaphragm provided in an embodiment of the present application.
[0052] Based on a general inventive concept, the present application provides a method for preparing a lithiation separator as described in any one of the above embodiments, the method comprising:
[0053] S1, mixing an inorganic filler, polyvinylidene fluoride and a solvent to obtain a mixed slurry;
[0054] In some embodiments, the mass ratio of the inorganic filler to polyvinylidene fluoride is (7-9):(1-3).
[0055] In some embodiments, the mass concentration of the polyvinylidene fluoride is 30 mg / mL to 70 mg / mL.
[0056] Polyvinylidene fluoride (PVDF) is used as a binder for the coating and a medium for lithium ion conduction. PVDF has good solubility and film-forming properties. The solvent can be selected to dissolve PVDF and form a uniform mixed slurry, such as N-methylpyrrolidone (NMP). The mass ratio of inorganic filler to polyvinylidene fluoride is limited to (7-9): (1-3), and the mass concentration of polyvinylidene fluoride is 30 mg / mL-70 mg / mL to ensure the mechanical strength and lithium ion conduction performance of the coating. Exemplarily, the mass ratio of inorganic filler to polyvinylidene fluoride can be 7:3, 8:2, 9:1, etc., and the mass concentration of polyvinylidene fluoride can be 30 mg / mL, 34 mg / mL, 40 mg / mL, 45 mg / mL, 50 mg / mL, 60 mg / mL, 65 mg / mL, 70 mg / mL, etc.
[0057] S2, applying the mixed slurry to at least a portion of the base film to form the coating to obtain a composite diaphragm;
[0058] S3, electrochemically pre-lithiating the composite membrane to obtain a lithiated membrane.
[0059] Electrochemical pre-lithiation is used to embed Li in the coating. + , in order to improve the lithium ion conductivity and cycle stability of the lithiated separator.
[0060] The product prepared by the method for preparing the lithiation membrane is the above-mentioned lithiation membrane. The chemical composition and microstructure of the lithiation membrane prepared by the method for preparing the lithiation membrane can refer to the above-mentioned embodiment. Since the method for preparing the lithiation membrane adopts part or all of the technical solutions of the lithiation membrane embodiment, it at least has all the beneficial effects brought by the technical solutions of the lithiation membrane embodiment, which will not be repeated here one by one.
[0061] Based on a general inventive concept, the present application provides a lithium metal battery, wherein the lithium metal battery comprises the lithiated separator described in any one of the embodiments in the first aspect.
[0062] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0063] Example 1
[0064] This embodiment provides a lithiated diaphragm, and the preparation method of the lithiated diaphragm specifically includes the following steps:
[0065] Step 1. Preparation of PVDF solution:
[0066] Accurately weigh 100 mg of polyvinylidene fluoride (PVDF). Add PVDF to 1 mL of N-methylpyrrolidone (NMP). Use a magnetic stirrer to stir at a rate of 1000 r / min until PVDF is completely dissolved to form a uniform PVDF solution.
[0067] Step 2. Dispersion of inorganic filler:
[0068] Add 200 mg of inorganic filler (TiO2) to the PVDF solution. Use a mechanical stirrer to stir at 300 r / min for 24 h to ensure that the inorganic filler is evenly dispersed in the PVDF solution. Transfer the mixed solution to an ultrasonic bath and perform ultrasonic treatment for 30 min to further break up any agglomerates that may exist.
[0069] Step 3. Coating preparation:
[0070] Take a commercially available polypropylene (PP) diaphragm, whose surface has been cleaned to ensure that there is no dust and oil. Use a coating machine to evenly coat the mixed solution of PVDF and inorganic filler on the PP diaphragm at a coating speed of 10 cm / min to ensure that the coating thickness is consistent. Put the coated diaphragm into a blast drying oven and heat it at 60°C for 12 hours to remove the residual NMP solvent to obtain a composite diaphragm.
[0071] Step 4. Electrochemical pre-lithiation treatment:
[0072] To assemble the Li|Cu half-cell, the PP separator coated with inorganic fillers was placed between two lithium and copper foils.
[0073] Using a battery test system, the 2 The half-cell is discharged at a constant current density until the voltage decreases to complete the electrochemical pre-lithiation process. The pre-lithiation membrane is taken out and placed in a beaker filled with a pure electrolyte solvent (EC / DEC volume ratio 1:1) and soaked for 24 hours to wash away the lithium salt on the surface. The cleaned membrane is placed in an argon-filled glove box to dry naturally, or dried in a forced air drying oven at 40°C for 1 hour to obtain a lithiated membrane (named Li x TiO 2-δ @PP). Lithium of the lithiated separator x TiO 2-δ The loading amount is 0.7 mg / cm 2 , the coating thickness of the lithiated separator is 6 ± 0.5 μm.
[0074] Example 2
[0075] The difference between this embodiment and embodiment 1 is that the lithiated separator (named Li x TiO 2-δ @PP)Li x TiO 2-δ The loading amount is 1.2 mg / cm 2 , the coating thickness of the lithiated separator is 8 ± 0.5 μm.
[0076] Example 3
[0077] The difference between this embodiment and embodiment 1 is that the lithiated separator (named Li x TiO 2-δ @PP)Li x TiO 2-δ The loading amount is 1.6 mg / cm 2 , the coating thickness of the lithiated separator is 10±0.5μm.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that the composite diaphragm intermediate product is not subjected to electrochemical pre-lithiation treatment to obtain a composite diaphragm (named R-TiO2@PP).
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 1 is that the diaphragm is a common polypropylene diaphragm (named PP).
[0082] The performance of the lithiated diaphragms obtained in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the specific steps are as follows: All 2025 button cells were assembled in a glove box filled with argon (Mbraun brand, the concentration of oxygen and water is less than 0.5ppm). 1M LiPF6 was used as the electrolyte, the solvents were EC (ethylene carbonate) and DEC (diethyl carbonate), the volume ratio was 1:1, and 10% FEC (fluoroethylene carbonate) was added. The assembled batteries were tested for electrochemical performance using a LAND 8-channel tester, including but not limited to the open circuit voltage, charge and discharge behavior, cycle stability and coulombic efficiency of the battery. Before the test, the battery was properly pretreated, such as constant voltage pre-charging and aging process, to ensure that the battery reached a stable state. The battery performance was comprehensively evaluated using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), charge and discharge testing and other methods. The measurement results are as follows Figure 7 to Figure 10 And as shown in Table 1.
[0083] Figure 2 This is an optical photograph of the lithiated separator provided in Example 1 of the present application. Figure 2 It can be seen that the coating is uniform and smooth, and there are no cracks or defects.
[0084] Figure 3 Li on the lithiated diaphragm provided in Example 1 of the present application x TiO 2-δ TEM image of particles. Figure 3 It can be seen that TEM shows that Li x TiO 2-δ The structure exhibits amorphous characteristics.
[0085] Figure 4 Li on the lithiated diaphragm provided in Example 1 of the present application x TiO 2-δ XRD spectrum of particles. Figure 4 It can be seen that Li after electrochemical lithiation x TiO 2-δ The structure shows amorphous characteristics, the crystal diffraction peak weakens and moves to the low angle direction, which indicates that Li + Embedding.
[0086] Figure 5 The Li on the diaphragm provided in Example 1 and Comparative Example 1 of the present application x TiO 2-δ EPR spectra of particles and TiO2 particles. Figure 5 It can be seen that Li + Inducing high content of Ti 3+ The components and oxygen vacancies in Example 1 x TiO2-δ In the @PP sample, the characteristic peak of g = 2.003 is attributed to oxygen vacancies (V O ), which is related to the presence of oxygen vacancies and Ti 3+ -O - Related to the formation of free radicals.
[0087] Figure 6 The Li on the diaphragm provided in Example 1 and Comparative Example 1 of the present application x TiO 2-δ O1s high-resolution XPS spectra of particles and TiO2 particles. Figure 6 It can be seen that the O 1s spectrum shows three characteristic peaks, corresponding to lattice oxygen (O1), defect oxygen (O2) and chemically adsorbed oxygen (O3). x TiO 2-δ Compared with R-TiO2@PP of comparative example 1, the oxygen peak of @PP shifts to a higher binding energy direction, and the oxygen vacancies determined by the oxygen peak area ratio increase. x TiO 2-δ @The relative content of defective oxygen (O2) in PP increases, while the relative content of lattice oxygen (O1) decreases significantly.
[0088] Figure 7 This is a test diagram of a lithium symmetric battery using the separator provided in Example 1 and Comparative Example 2 of the present application. Figure 7 It can be seen that the horizontal axis represents the cycle time, and the vertical axis represents the polarization voltage. The results of the symmetrical battery show that: the Li x TiO 2-δ @PP diaphragm has good cycle performance.
[0089] Figure 8 CE diagrams of the diaphragms provided in Examples 1 to 3 and Comparative Examples 1 to 2 of the present application. Figure 8 It can be seen that the horizontal axis represents the number of cycles, and the vertical axis represents CE, with the first time CE is lower than 90% as the measurement standard. x TiO 2-δ Loading amount is >0 and ≤1.6mg / m 2 Within the range of , they all have a high CE retention ability, but with the increase of the load, the transmission distance and transmission resistance of lithium ions will increase, resulting in a decrease in transmission speed and a decrease in CE.
[0090] Fig. 9 This is a full battery test diagram of the diaphragm provided in Example 1 and Comparative Examples 1-2 of the present application. Fig. 9 It can be seen that the horizontal axis represents the number of cycles, the vertical axis (left) represents the discharge capacity, and the vertical axis (right) represents the CE. x TiO 2-δ@PP's Li(40μm)|NMC811 full cell test at 0.5C charge (0.5C) and 1.0C discharge (1D) rates, Li x TiO 2-δ @PP can achieve stable long cycle performance.
[0091] Fig.10 This is a rate performance test diagram of the diaphragm provided in Example 1 and Comparative Examples 1-2 of the present application. Fig.10 It can be seen that the horizontal axis represents the number of cycles, and the vertical axis represents the discharge capacity. As the current density increases from 0.2C to 3C, the Li x TiO 2-δ @PP helps achieve excellent rate performance.
[0092] Table 1 Cyclic stability of the membranes provided by the embodiments and comparative examples
[0093]
[0094] In addition, one or more technical solutions in the embodiments of the present application have at least the following technical effects or advantages:
[0095] In the embodiment of the present application, an amorphous Li x TiO 2-δ @PP multifunctional diaphragm (Li x TiO 2-δ @PP, (0≤x≤1; 0≤δ≤2), in the lean ester-based electrolyte (1.4μL / (mA hNMC811)), especially under the extreme conditions of high positive electrode loading and limited lithium resources (little lithium and no lithium anode), high average CE and long cycle life are achieved. The coating structure has highly uniform ion channels at the nanoscale, which is conducive to the uniform transport of Li+. + Embedding, Ti 4+ Reduced to Ti 3+ , the crystal structure of TiO2 is missing, resulting in a large number of oxygen vacancies,
[0096] The enhanced reducibility allows the natural passivation layer on lithium metal to react preferentially, reducing the nucleation overpotential. At the same time, the construction of a diaphragm with multiple oxygen vacancy sites is conducive to the dissociation of lithium salts, increasing the number of lithium ion migrations and promoting the uniform distribution of lithium ions. The Lego-like structure formed after electroplating effectively protects the diaphragm from being penetrated by dendrites.
[0097] In the present embodiment, the prepared Li x TiO 2-δ@PP achieved a high average CE of 94.68% and a stable cycling of over 3000 h in Li|Cu half-cell and Li|Li symmetric cell, respectively. 2 LiNi 0.8 Mn 0.1 Co 0.1 After coupling the (NMC811) positive electrode, the full battery has more than 140 stable cycles and an average CE of 99.7% under the condition that the negative / positive electrode area capacity ratio (N / P ratio) is less than 2. Even under the extreme condition that the N / P ratio is less than 0.5, it still has high capacity retention and average CE.
[0098] In the examples of this application, based on low-cost raw materials and simple preparation methods, the lithiated separator can be applied on a large scale. The coulombic efficiency and cycle stability of the battery are effectively improved through electrochemical pre-lithiation treatment. This study provides an effective strategy for achieving high safety, high energy density and long life LMB in ester-based electrolytes.
[0099] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A lithiated diaphragm, comprising: Basement membrane; as well as A coating layer is attached to at least a portion of the separator, wherein the coating layer contains Li + The embedded inorganic + The chemical formula of the embedded inorganic substance is Li x A a B b-δ , where A a B b Indicates inorganic matter, 0<x<a; 0<δ<b.
2. The lithiated separator according to claim 1, characterized in that The Li + The embedded inorganic matter has an amorphous structure.
3. The lithiated separator according to claim 2, characterized in that The Li + The embedded inorganic substances include: Li x TiO 2-δ , Li x ZnO 1-δ , Li x SnO 2-δ and Li x MnO 2-δ At least one of .
4. The lithiated separator according to claim 3, characterized in that The Li + The embedded inorganic loading is > 0 and ≤ 1.6 mg / m 2 .
5. The lithiated separator according to claim 1, characterized in that The thickness of the coating is >0 and ≤10 μm.
6. The lithiated separator according to claim 1, characterized in that The base film is a polyolefin membrane, and the polyolefin membrane includes: a polyethylene membrane, a polypropylene membrane, and a polyethylene and polypropylene composite membrane.
7. A method for preparing a lithiated separator according to any one of claims 1 to 6, characterized in that: The method comprises: Mixing an inorganic filler, polyvinylidene fluoride and a solvent to obtain a mixed slurry; Applying the mixed slurry to at least a portion of the base film to form the coating to obtain a composite diaphragm; The composite membrane is electrochemically pre-lithiated to obtain a lithiated membrane.
8. The method according to claim 6, characterized in that The mass ratio of the inorganic filler to polyvinylidene fluoride is (7-9):(1-3).
9. The method according to claim 6, characterized in that The mass concentration of the polyvinylidene fluoride is 30 mg / mL to 70 mg / mL.
10. A lithium metal battery, characterized in that: The lithium metal battery comprises the lithiated separator according to any one of claims 1 to 6.